FiO2 Before Surfactant, but Not Time to Surfactant, Affects Outcomes in Infants With Respiratory Distress Syndrome - Kruczek, Piotr; Krajewski, Paweł; Hożejowski, Roman; Szczapa, Tomasz (Frontiers in Pediatrics, 2021)
Aim: To establish the impact of oxygen requirement before surfactant (SF) and time from birth to SF administration on treatment outcomes in neonatal respiratory distress syndrome (RDS). Methods: We conducted a post hoc analysis of data from a prospective cohort study of 500 premature infants treated with less invasive surfactant administration (LISA). LISA failure was defined as the need for early (<72 hours of life) mechanical ventilation (MV). Baseline clinical characteristic parameters, time to SF, and fraction of inspired oxygen (FiO2) prior to SF were all included in the multifactorial logistic regression model that explained LISA failure. Results: LISA failed in 114 of 500 infants (22.8%). The median time to SF was 2.1 hours (IQR: 0.8 – 6.7), and the median FiO2 prior to SF was 0.40 (IQR: 0.35 – 0.50). Factors significantly associated with LISA failure were FiO2 prior to SF (OR 1.03, 95% CI 1.01 – 1.04) and gestational age (OR 0.82, 95 CI 0.75 – 0.89); both p <0.001. Time to SF was not an independent risk factor for therapy failure (p=0.528) or the need for MV at any time during hospitalization (p=0.933). Conclusions: The FiO2 before SF, but not time to SF, influences the need for MV in infants with RDS. While our findings support the relevance of FiO2 in SF prescription, better adherence to the recommended FiO2 threshold for SF (0.30) is required in daily practice.